Planning of Granular Activated Carbon Unit to Remove Ammonia and TSS at IPLT X, Kota Jakarta - Sri Dewi Handayani; Yesaya Emeraldy Priutama; Intan Rahmalia; Farhan Muhammad Hilmi; Reifaldy Tsany Betta Aryanto; Evi Siti Sofiyah; Ariyanti Sarwono; I Wayan Koko Suryawan (Equilibrium)
ABSTRACT. Fecal sludge can be treated by conventional treatment such as pond stabilization which is commonly used to reduce organic concentrations. However, nutrients such as NH3 are still widely measured in the effluent. One of the sewerage treatments in the city of Jakarta, for example, experienced this condition. This study aims to design an appropriate technology to increase the efficiency of nutrient ammonia and total suspended solid (TSS) removal at Duri X IPLT. The unit added in the selected effluent treatment is Granular Activated Carbon (GAC). Design considerations are the characteristics of activated carbon, operating conditions (discharge and contact time), and operating mode (fixed-, expanded-, or fluidized-bed, pumped, or gravity flow). The Carbon Usage Rate for removing ammonia and TSS is 1.384 g/L and 0.378 g/L, respectively. Maintenance is required so that the granular activated carbon (GAC) unit can continue operating and functioning properly. Blockages in carbon transport pipes can occur in many pipes. This can occur due to a too-small pipe, a short bend radius of the pipe, a lack of speed, and a lack of cleaning of the pipe. The eroded pipe is also a common problem that often occurs in unlined mild steel and fiberglass reinforced plastic (FRP), usually in sharp bends.